Document Archiving Information System Design Using VB.NET, Banda Aceh Sharia Court - Rahmadi, Khairul; Mulyati, Dewi; Hidayat, Taufik (Divisi Riset, Lembaga Mitra Solusi Teknologi Informasi (L-MSTI), 2022)
The document archiving information system at the Banda Aceh Sharia Court currently faces efficiency challenges due to its reliance on conventional document storage methods, such as filing cabinets and manual record-keeping in books. This results in suboptimal accuracy levels. Additionally, significant space allocation is required for storage solutions like filing cabinets, folders, and shelves. Another issue is the time-consuming nature of document retrieval due to disorganized arrangements. From a cost perspective, there are additional expenses for the maintenance and upkeep of archive storage areas. This research aims to address the following questions: How can a more efficient Document Archiving Information System be designed for the Banda Aceh Sharia Court? Will the implementation of this system enhance the speed and accuracy of available information? What is the process for presenting this Document Archiving Information System at the Banda Aceh Sharia Court? The focus of this study is on developing an information system that provides alternative solutions to document archiving challenges using the Visual BASIC.NET approach. Furthermore, the study highlights the procedures for storing and retrieving archives within the document archiving information system at the Banda Aceh Sharia Court. The waterfall method, also known as the sequential method, was employed in the design of the Document Archiving Information System. Data collection was conducted through various research methods, including observation, interviews, and literature studies. The tools used in the application development include Microsoft Visual Basic.NET for interface design and Microsoft Office Access as the database management system. Testing results indicate that the developed system meets the identified needs, including efficient data input processes and accurate reporting